2023
DOI: 10.3390/polym15142988
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity of 3D-Printed Polymer Elements

Abstract: During this study, the resistivity of electrically conductive structures 3D-printed via fused filament fabrication (FFF) was investigated. Electrical resistivity characterisation was performed on various structural levels of the whole 3D-printed body, starting from the single traxel (3D-printed single track element), continuing with monolayer and multilayer formation, finalising with hybrid structures of a basic nonconductive polymer and an electrically conductive one. Two commercial conductive materials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Stankevich et al observed a decrease in resistivity as nozzle diameter increased for a CB-PLA composite [ 11 ]. The observed behavior may have been due to the smaller nozzle’s increased susceptibility to clogging, or a restricted flow cross-section, resulting in uneven polymer melt application and higher variability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stankevich et al observed a decrease in resistivity as nozzle diameter increased for a CB-PLA composite [ 11 ]. The observed behavior may have been due to the smaller nozzle’s increased susceptibility to clogging, or a restricted flow cross-section, resulting in uneven polymer melt application and higher variability.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of nozzle diameter has rarely been investigated, as shown in the table (literature review). Previous studies in this field have been conducted by Stankevich et al (using PLA/CB and PVDF/G), Dembek et al (using PLA/CNT), and Nassar et al (using PCL/copper) [ 11 , 20 , 34 ]. The DoE in this study matched that of Nowka et al in [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As material ProtoPasta conductive PLA with a diameter of 1.75 mm is used [50]. This material has a reported resistivity of 0.06 Ω m to 0.34 Ω m, depending on the print settings and geometry [44], [51]- [53]. The samples are squares of 30 x 30 x 0.2 mm, printed on top of oxidized silicon wafers, where a spray is used to improve adhesion (3DLAC).…”
Section: A Fabricationmentioning
confidence: 99%